Analisis Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Melanjutkan Studi Pada Program Pendidikan Profesi Akuntansi(Studi Empiris pada Mahasiswa Akuntansi Universitas Muhammadiyah Surakarta Angkatan 2012) - Prakoso, Whowhok, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2016)
This study aims to identify and analyze the factors that affect the interest ofstudents to continue on the study on professional education programs akuntansi.Populasi in this study were students of Accounting Studies Program Faculty of Economics and Business, University of Muhammadiyah Surakarta force in 2012. While the sample is student of Accounting Faculty of Economics and Business, University of Muhammadiyah Surakarta class of 2012. This research uses convinience sampling techniques in conducting research, in order to obtain a sample of 82 students. Data analysis technique used is multiple linear regression. The results of this study indicate that student readiness, motivation, professional commitment and awareness of students significant effect on the interests of students continue their studies in the accounting profession program.